Local anisotropy in single crystals of zeotypes with the MFI framework structure evidenced by polarised Raman spectroscopy. Issue 3 (2nd January 2020) - Martinelli, Anna; Creci, Simone; Vavra, Szilvia; Carlsson, Per-Anders; Skoglundh, Magnus
Abstract : Polarised Raman spectroscopy is used to reveal the orientation of specific T–O–T bonds in singe crystals of ZSM-5 and silicalite-1. Abstract : Polarised Raman spectroscopy is used to characterise the local structure in single crystals of zeotypes, namely silicalite-1 and ZSM-5, which share the MFI framework structure. Attributes favourable for applying polarised Raman spectroscopy are the orthogonal axes of these single crystals and their size, i.e. 10 to 30 micrometers in all three directions. We show that the intensity of certain vibrational modes in silicalite-1 depends on the polarisation of the incident light, reflecting the anisotropic character of the molecular bonds contributing to these vibrations. Using these observations, and by estimating the depolarisation ratio ( ρ ) and the pseudo-order factor ( f ), we propose a more accurate assignment of the Raman active modes. More precisely, Raman intensities peaked at 294, 360, 383 and 472 cm −1 are attributed to bending modes in 10-, 6-, 5- and 4-membered rings, respectively. In the region of stretching modes, the vibration at 832 cm −1 is assigned to Si–O–Si bonds shared between 5-membered rings, which have an orientation parallel to the a -axis of the crystal. By virtue of having a strongly polarised character, the modes at 472 and 832 cm −1 can be used as orientational indicators. The proposed assignment is supported by the good agreement between experimental and simulated polar plots, where Raman intensities are plotted as a function of the polarisation angle of the incident light. Finally, upon partial substitution of Si atoms by Al, the crystalline structure is maintained and almost no spectroscopic changes are observed. The only significant difference is the increased width of most vibrational modes, which is consistent with the local lower symmetry. This is also seen in the angular dependence of selected vibrational modes that compared to the case of pure silicalite-1 appear less polarised. In the Raman spectrum of ZSM-5 a new feature at 974 cm −1 is observed, which we attribute to Al–OH stretching. In the high frequency range, the O–H stretching modes are observed which arise from the Si–O(H)–Al Brønsted acid sites. The intensity of the characteristic mode at 3611 cm −1 reveals an anisotropic character as well, which is in line with previous findings from solid state NMR that Al atoms distribute nonrandomly within the MFI framework structure.